Stable isotopes reveal human influences on southern New Zealand soils. (July 2017) - Rogers, K.M.; Turnbull, R.E.; Martin, A.P.; Baisden, W.T.; Rattenbury, M.S.
Abstract: A multi-isotopic soil study across a southern New Zealand transect has been undertaken as part of a geochemical baseline survey to identify human impacts on New Zealand's landscape and characterise different land uses and anthropogenic effects. Carbon, nitrogen and sulphur isotopes from two soil depths (0–30 and 50–70 cm) were acquired across a variety of land uses (including pristine national parks, urban centres, intensively farmed pastoral land), climates (dry <500 mm annual rainfall to wet >6000 mm annual rainfall), altitude (sea level to >2300 m above sea level) and soil parent material lithology (sandstone, schist, basalt). Detrital organic matter accumulated more in lowlands than at higher altitudes with higher carbon and nitrogen contents found in river valleys. Carbon isotopes clearly differentiated between drier higher altitude or open pastoral sites (more positive values) and wetter forested sites (more negative values). Nitrogen isotopes reflect anthropogenic human influence with elevated values around urban and intensively farmed sites, and lower values characterising indigenous forests and pristine sites. Sulphur isotopes either show more positive values, typical of fertilisers, rain or sea spray in open pastoral sites, or more negative values consistent with weathered geological sources such as metamorphic sulphides found in schist in some river valley sites. The study demonstrates that regional isotope studies are a potential tool to understand the long and short term impacts on landscapes, and may be useful for future mineral exploration, urban health studies, agricultural site remediation, and land use control and regulation. Highlights: Large scale, detailed isotopic transect study across southern New Zealand (n = 134 samples). Organic matter accumulates more in river valleys than at higher altitudes. Carbon isotopes differentiate clearly between drier sites (more positive values) and wetter sites (more negative values). Nitrogen isotopes reflect anthropogenic human activities while sulphur isotopes are attributed to marine sea spray, fertilisers or weathered geological sources. Regional isotopes are a potential tool to understand the long and short term impacts on landscapes.